Covid-19 impact on companies’ dividend policies and corporate characteristics: evidence from the Shanghai Stock Exchange - Lu, Li (2022)
This paper examines the Covid-19 impact on the dividend policies and corporate characteristics of Chinese companies listed on the Shanghai Stock Exchange. The study uses all the non-financial listed companies’ data for the period from 2018 to 2021, and conduct the research from both the short-term the long-term time interval, namely 2019 versus 2020, 2020 versus 2021 and 2018/19 versus 2020/21. In addition to the multiple regression applied to the panel data with the fixed effect model, the Difference-in-Difference model (DID) will be applied to accurately estimate the intervention of Covid-19 on different aspects of companies while not influencing others. Moreover, the robustness test will be used to ensure the consistency and stability of the results and conclusions in the study. The study finds out that the dividend policy of Chinese listed companies has been hardly influenced by Covid-19 in both time intervals. Besides, the outbreak of Covid-19 has indeed brought some negative impacts on companies' characteristics, except for the investment, in the long-term time interval. For the short-term time interval, there is a negative correlation between Covid-19 and firm characteristics in the 2019 versus 2020 subgroup and the influences of Covid-19 were mixed in 2020 versus 2021 subgroup.